Extracellular Matrix Mimicking Nanofibrous Scaffolds Modified With Mesenchymal Stem Cell-Derived Extracellular Vesicles for Improved Vascularization - Hao, Dake; Swindell, Hila Shimshi; Ramasubramanian, Lalithasri; Liu, Ruiwu; Lam, Kit S.; Farmer, Diana L.; Wang, Aijun (Frontiers in Bioengineering and Biotechnology, 2020)
The network structure and biological components of natural extracellular matrix (ECM) are indispensable for promoting tissue regeneration. Electrospun nanofibrous scaffolds have been widely used in regenerative medicine to provide structural support for cell growth and tissue regeneration due to their natural ECM mimicking architecture, however, they lack biological functions. Extracellular vesicles (EVs) are potent vehicles of intercellular communication due to their ability to transfer RNAs, proteins, and lipids, thereby mediating significant biological functions in different biological systems. Matrix-bound nanovesicles (MBVs) are identified as an integral and functional component of ECM bioscaffolds mediating significant regenerative functions. Therefore, to engineer EVs modified electrospun scaffolds, mimicking the structure of the natural EV-ECM complex and the physiological interactions between the ECM and EVs, will be attractive and promising in tissue regeneration. Previously, using one-bead one-compound (OBOC) combinatorial technology, we identified LLP2A, an integrin α4β1 ligand, which had a strong binding to human placenta-derived mesenchymal stem cells (PMSCs). In this study, we isolated PMSCs derived EVs (PMSC-EVs) and demonstrated they expressed integrin α4β1 and could improve endothelial cell (EC) migration and vascular sprouting in an ex vivo rat aortic ring assay. LLP2A treated culture surface significantly improved PMSC-EV attachment, and the PMSC-EV treated culture surface significantly enhanced the expression of angiogenic genes and suppressed apoptotic activity. We then developed an approach to enable ‘click chemistry’ to immobilize LLP2A onto the surface of electrospun scaffolds as a linker to immobilize PMSC-EVs onto the scaffold. The PMSC-EV modified electrospun scaffolds significantly promoted EC survival and angiogenic gene expression, such as KDR and TIE2, and suppressed the expression of apoptotic markers, such as caspase 9 and caspase 3. Thus, PMSC-EVs hold promising potential to functionalize biomaterial constructs and improve the vascularization and regenerative potential. The EVs modified biomaterial scaffolds can be widely used for different tissue engineering applications.